2022
DOI: 10.1101/2022.11.12.516113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrovascular damage caused by the gut microbe/host co-metabolitep-cresol sulfate is prevented by blockade of the EGF receptor

Abstract: Chronic kidney disease is linked to impaired cognitive function and increased neurovascular disease risk even after correction for classical risk factors. The mechanism(s) underlying these links are unclear but may involve interactions of uraemic toxins with the blood-brain barrier (BBB). Here, we studied how the major uraemic toxinp-cresol sulfate (pCS) could affect BBB integrity. Exposure of human hCMEC/D3 endothelial cells to pCS dose-dependently increased paracellular permeability and disrupted intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…We analyzed BBB permeability only at the end of the experiment, and we cannot determine whether the observed differences between the cohorts pre-existed or resulted from SPS exposure. Yet, recent studies reported elevated levels of toxic microbial metabolites, such as p-crestol, capable of disrupting BBB integrity, which coincided with trauma-induced gut microbial alterations ( Laudani et al, 2023 ; Shah et al, 2022 ). This further highlights the importance of gut microbial metabolites in the gut-brain communication axis.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed BBB permeability only at the end of the experiment, and we cannot determine whether the observed differences between the cohorts pre-existed or resulted from SPS exposure. Yet, recent studies reported elevated levels of toxic microbial metabolites, such as p-crestol, capable of disrupting BBB integrity, which coincided with trauma-induced gut microbial alterations ( Laudani et al, 2023 ; Shah et al, 2022 ). This further highlights the importance of gut microbial metabolites in the gut-brain communication axis.…”
Section: Discussionmentioning
confidence: 99%
“…This translates into increased production of p-cresol and lipopolysaccharides (LPS), as well as increased degradation of intestinal mucus, suggesting enhanced permeability of the gut cell wall. Of interest here, the uraemic toxin p-cresol sulfate (pCS) is known to increase endothelial permeability and has been recently linked to cerebrovascular damage due to its disruptive actions on BBB integrity [61,137]. Other studies, although lacking the molecular mechanisms linked to the GBA and related derived metabolites, have evaluated the effects of olive oil polyphenols, major components of the Mediterranean diet (Med Diet).…”
Section: Clinical Evidencementioning
confidence: 99%
“…Some of these metabolites are beneficial such as indoles that regulate the IB function and immune response, and bile acids and TMA that maintain glycolipid homeostasis. Contrarywise, others are detrimental such as LPS which is an immune system disrupter and circulating uremic toxins derived from the digestion of dietary amino acids that have recently been shown to impair BBB integrity and alter brain activity (p-cresol sulfate and 4-ethylphenyl sulfate) [ 58 , 59 ].…”
Section: Formation Composition and Role Of Gut Microbiotamentioning
confidence: 99%